Follicular lymphoma in Taiwan: a low frequency of t(14;18), with grade 3A tumours more closely related to grade 3B than to low‐grade tumours. Issue 1 (30th April 2013) - Chang, Sheng‐Tsung; Lu, Yi‐Hsuan; Lu, Chin‐Li; Kuo, Szu‐Yin; Liu, Hongxiang; Lin, Shu‐Hui; Win, Khin Than; Hsieh, Yen‐Chuan; Chuang, Shih‐Sung
<x xml:space="preserve">Abstract</x> Aims To investigate t(14;18)/IGH–BCL2 in follicular lymphoma (FL) cases from Taiwan. Methods and results We retrospectively studied 93 consecutive cases, using immunohistochemistry and fluorescence in‐situ hybridization (FISH). Fifty‐nine (63%) tumours were low‐grade (LG) and 34 (37%) were high‐grade (HG; 24% FL3A and 13% FL3B). FISH showed IGH, BCL2 and BCL6 rearrangements in 59%, 47% and 11% of cases, respectively, and MYC rearrangement in 5% of FL3A tumours and 25% of FL3B tumours. The translocation partner of all BCL2 rearrangements was IGH, with IGH–BCL2 fusion in 63% of LG tumours and 18% of HG tumours. LG tumours were enriched with a CD10+/bcl‐2+/MUM1‐ phenotype, and were frequently associated with BCL2 rearrangement but less commonly with BCL6 rearrangement. FL3A tumours were more closely related to FL3B tumours than to LG tumours in immunophenotype and genetic aberrations. There was no statistically significant difference between grade 1 and two tumours, between FL3A and FL3B tumours or between nodal and extranodal tumours in immunophenotypic or FISH findings. The cumulative survival rate was higher in LG FL patients with IGH–BCL2 translocation than in those without rearrangement. Conclusions In Taiwan, FL3A tumours were more closely related to FL3B tumours than to LG tumours, and a literature review showed that the frequency of t(14;18)/IGH–BCL2 in FL in Taiwan is among the lowest in the world.